Pergeseran Semantik/Semantic Shifting - Mahridawati Mahridawati (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2018)
Semantics in this case take a great role to decipher the meanings of the sign language. In this universe, the signs of language have undergone changes that result in semantic shifting 'semantic shift'. The semantic shift, hereinafter referred to as the change of meaning, is not a coincidence, it is all the causes of the change. The changes that occur in the sign language synergize with the developments that occur in this universe. The development of technology and human culture can not be denied has contributed to the change of meaning. Many signs that initially have no meaning that refers to a particular technology in its development of the mark refers to a particular technology. Changes in the meaning of the sign language is interesting to examine, especially the sign of the language that changed due to the development of science and technology, because with the study writers are motivated to more in search of the initial meaning of the origin of the sign before it developed into a new sign by the cause of new technologies that require naming the technology.